2021
DOI: 10.23887/ekuitas.v9i1.32710
|View full text |Cite
|
Sign up to set email alerts
|

Gerakan Literasi Finansial di SMA Kabupaten Kubu Raya Kalimantan Barat

Abstract: The purpose of this study was to determine how the financial literacy movement with indicators of class basis, school cultural basis and community basis in Senior High School Kubu Raya Regency, West Kalimantan. The method used was a descriptive method with a survey form. The research subject was an economic teacher, data collection was done by interview and a questionnaire using google form. The data analysis step used the Interactive Analysis Model from Miles and Huberman. The technique of checking the validi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The 2018 PISA results show that Indonesian students' financial literacy skills are ranked 20th out of 20 countries that participated, with a score of 388 (the only country with a score < 400) (OECD, 2020). Meanwhile, the results of the 2020 OJK survey show that the financial literacy ability of the Indonesian people only reached 38.030% (< 50%) (Kuswanti & Ulfah, 2021;Otoritas Jasa Keuangan, 2020). Therefore, the financial literacy ability of class XI students of public high schools in Soppeng Regency in solving math problems is still in a low category.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2018 PISA results show that Indonesian students' financial literacy skills are ranked 20th out of 20 countries that participated, with a score of 388 (the only country with a score < 400) (OECD, 2020). Meanwhile, the results of the 2020 OJK survey show that the financial literacy ability of the Indonesian people only reached 38.030% (< 50%) (Kuswanti & Ulfah, 2021;Otoritas Jasa Keuangan, 2020). Therefore, the financial literacy ability of class XI students of public high schools in Soppeng Regency in solving math problems is still in a low category.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Indonesian students' financial literacy skills were ranked last out of the 20 participating countries with a score of 388 (OECD, 2020). The Financial Services Authority (OJK) survey revealed that the financial literacy ability of the Indonesian people only reached 38.03% (Kuswanti & Ulfah, 2021). Related to these data, Indonesian students' mathematical and financial literacy abilities are still relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…So if there are guests from outside the school can see the results of the children's handicrafts. The financial habituation is an introduction to how to manage and market a product it makes (Belzer, 2017;Kuswanti & Ulfah, 2021;Laila et al, 2019).…”
Section: Discussionmentioning
confidence: 99%